Respostas

  • Usuário do Brainly
2014-05-27T22:25:05-03:00

(4,2x² :  0,7x)- (0,49x :0,7x)

6x-0,7

A melhor resposta!
2014-05-27T22:35:58-03:00
(4,2x²-0,49x):0,7x =

4,2 x² - 0,49x : 0,7

    
 fazer por parte

4,2     |__0,7___        elimina as VIRGULAS do 4,2 com 0,7  fica 42 e 07

42   |__07___
   0        6


outro

0,49   |__0,7 ____

04,9   |__07____

049    |__70____

49      |__70___
           0,

490   |__70____
   00         0,7 


então

(4,2x²-0,49x):0,7x =

   4,2x² - 0,49x     |__0,7x____
- 4,2x²                     6x  - 0,7      Q(x) = quociente = 6x - 0,7
---------
       0  - 0,49x
           +0,49x
          -----------
                  0    R(x) = resto = 0  
1 5 1